Pemberdayaan Masyarakat Di Desa Berjo Kabupaten Karanganyar Melalui Pelatihan Pembuatan Teh Daun Alpukat Sebagai Antidiabetes - Andriani Noerlita Ningrum; Anita Dewi Lieskusumastuti; Kiki Puspitasary; Vallina Laurensia Indikaningrum; Aiko Nurrahma Anjani (Pakis Journal Institute, 2024)
Diabetes mellitus is an increasing global health issue, with type 2 diabetes being the most common. Conventional treatments are often costly and have side effects, necessitating affordable and safer alternatives. Avocado leaves (Persea americana), rich in bioactive compounds such as polyphenols, have shown potential as a natural antidiabetic remedy. A community empowerment program was conducted in Dusun Selorejo, Karanganyar Regency, involving 50 participants trained to process avocado leaves into herbal tea. The program included educational sessions and practical workshops, followed by evaluations through observations and questionnaires to assess improvements in knowledge and skills. The program successfully increased community engagement and knowledge about the health benefits of avocado leaf tea. Participants showed significant improvements in understanding and skills related to tea preparation, indicating the program's effectiveness in promoting natural and affordable diabetes treatment alternatives.